2021
DOI: 10.1007/s00213-021-05776-0
|View full text |Cite
|
Sign up to set email alerts
|

The intoxicated co-witness: effects of alcohol and dyadic discussion on memory conformity and event recall

Abstract: Rationale Co-witness discussion is common and often witnesses are under the influence of alcohol. As such, it is important to understand how such factors may influence eyewitness testimony. Objectives We combined a co-witness memory paradigm with an alcohol administration paradigm to examine the influence of alcohol and dyadic discussion on remembering a mock crime. Methods Intoxicated and sober dyads discussed a pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Since researchers began to investigate the effects of alcohol on eyewitness memory, the results have been mixed, but so have the research methods. The to-be-remembered stimuli have included mock crime videos (e.g., Bartlett et al, 2021;Crossland et al, 2016;Hagsand et al, 2013aHagsand et al, , 2013bHagsand et al, , 2017, live staged events (e.g., Altman, McQuiston, et al, 2019;Mindthoff et al, 2019;Schreiber Compo et al, 2012), stories (e.g., Mindthoff et al, 2021), and picture slides (e.g., Harvey et al, 2013a;Harvey & Sekulla, 2021). Participants' memory for faces has been assessed with show-ups (e.g., Altman, McQuiston et al, 2019;Dysart et al, 2002) and line-ups (e.g., Altman et al, 2018;Hagsand et al, 2013b;Flowe et al, 2017), and their memory for events has been assessed via free recall (e.g., Evans et al, 2019;Hagsand et al, 2017;Hildebrand Karlén et al, 2017) and with cued recall interviews (e.g., Hagsand et al, 2017;Schreiber Compo et al, 2017).…”
Section: Applied Research On Alcohol's Effect On Witness Memorymentioning
confidence: 99%
“…Since researchers began to investigate the effects of alcohol on eyewitness memory, the results have been mixed, but so have the research methods. The to-be-remembered stimuli have included mock crime videos (e.g., Bartlett et al, 2021;Crossland et al, 2016;Hagsand et al, 2013aHagsand et al, , 2013bHagsand et al, , 2017, live staged events (e.g., Altman, McQuiston, et al, 2019;Mindthoff et al, 2019;Schreiber Compo et al, 2012), stories (e.g., Mindthoff et al, 2021), and picture slides (e.g., Harvey et al, 2013a;Harvey & Sekulla, 2021). Participants' memory for faces has been assessed with show-ups (e.g., Altman, McQuiston et al, 2019;Dysart et al, 2002) and line-ups (e.g., Altman et al, 2018;Hagsand et al, 2013b;Flowe et al, 2017), and their memory for events has been assessed via free recall (e.g., Evans et al, 2019;Hagsand et al, 2017;Hildebrand Karlén et al, 2017) and with cued recall interviews (e.g., Hagsand et al, 2017;Schreiber Compo et al, 2017).…”
Section: Applied Research On Alcohol's Effect On Witness Memorymentioning
confidence: 99%
“…On this basis, research has focused on elucidating the effects of alcohol intoxication on eyewitness memory accuracy. In laboratory studies using moderate doses of alcohol, studies suggest that intoxicated witnesses are less complete in their recall 10.3389/fpsyg.2022.983681 Frontiers in Psychology 02 frontiersin.org (Schreiber Compo et al, 2011), but also no less accurate (Flowe et al, 2019) and no more prone to reporting false information (Compo et al, 2012;Flowe et al, 2019;Bartlett et al, 2021, for a meta-analysis, see Jores et al, 2019). Also, intoxicated witnesses show least impairment in their recall accuracy and are less prone to suggestibility when recalling immediately compared to after a delay (Evans et al, 2017;Schreiber Compo et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Intoxicated participants also appear to be less confident in their recollections compared to sober controls (Crossland et al 2016;Flowe et al 2017). The majority of lab studies did not find alcohol-related differences in individual's suggestibility using misinformation paradigms (Bartlett et al 2021;Flowe et al 2019;Thorley & Christiansen 2018) or the Gudjonsson Suggestibility Scale (Mindthoff et al 2021). Evans et al (2019) found that intoxicated participants were only more vulnerable to incorrect suggestions when tested after a delay.…”
mentioning
confidence: 99%
“…Findings from lab studies using low to moderate doses of alcohol (blood alcohol concentration [BAC] < 0.08%) suggest that acute intoxication may lead participants to produce less complete memory accounts (i.e. recalling fewer correct details overall) without negatively impacting the accuracy of individual’s recall (Bartlett et al 2021 ; Flowe et al 2016 ; Hagsand et al 2017 ). Intoxicated participants also appear to be less confident in their recollections compared to sober controls (Crossland et al 2016 ; Flowe et al 2017 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation